Pengaruh Lingkungan Sosial, Ekspektasi Pendapatan, dan Fleksibilitas Kerja Terhadap Minat Menjadi Pemasar Afiliasi - Nailah Nasywa Suci; Saniatun Nurhasanah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to examine the influence of social environment, income expectations, and work flexibility on the interest of the Jabodetabek community in pursuing a career as affiliate marketers. This research employs a descriptive quantitative approach. Additionally, purposive sampling is utilized for the sampling process, with criteria targeting individuals aged at least 15 years in the Jabodetabek area who are currently involved in or have an interest in becoming affiliate marketers. Data were successfully collected from 387 respondents and analyzed using multiple linear regression analysis with the assistance of IBM SPSS 22 software. The findings indicate that the social environment variable has a positive and significant effect on the interest of the Jabodetabek community in becoming affiliate marketers. Similarly, the income expectation variable positively and significantly influences their interest, as does the work flexibility variable. Furthermore, the study demonstrates that the social environment, income expectations, and work flexibility collectively have a positive and significant impact on the interest of the Jabodetabek community in pursuing affiliate marketing. This study carries important practical implications for businesses, digital platforms, and affiliate marketing programs. Companies can leverage social influence by fostering supportive communities, promoting success stories, and encouraging peer recommendations to attract new affiliates.